Field and laboratory testing of products for control of European canker (Neonectria galligena) - Spires, A.G.; Fowler, S.R. (New Zealand Plant Protection, 2012)
European canker of apples caused by the fungus Neonectria galligena is a serious disease of apples throughout New Zealand Previously this pathogen was confined to the warm wet Waikato and Auckland districts In recent years the disease has become well established in Motueka and in the last three seasons has become prevalent in the Hawkes Bay Inoculum is present in the orchard throughout the year and any wound no matter how small is likely to become infected To control this pathogen inoculum levels in the orchard have to be reduced This involves treating whole trees post harvest and at leaf fall as well as pruning wounds and excision and treatment of active cankers Numerous fungicides were screened on agar for activity against N galligena and few exhibited strong inhibition of mycelial growth Manate thiophanate methyl chlorothanil dodine thiram slaked lime euparen multi copper oxychloride and captan were not effective whereas tebuconazole benomyl octhilinone and OM4 strongly inhibited growth Late season application of benomyl is ruled out because of the possible development of fungal resistance Field trials have demonstrated the effectiveness of paints/dressings containing tebuconazole and octhilinone at protecting pruning wounds and for application to excised stem cankers